Development of IoT Based Smart Grid System for Monitoring And Management of Electrical Energy Distribution - Sianturi, Barata Mandala; Satria, Beni; Tarigan, Amani Darma (Cattleya Darmaya Fortuna, 2025)
This study aims to develop a smart grid system based on the Internet of Things (IoT) to improve efficiency and sustainability in monitoring and managing electrical energy distribution. Smart grid is a modern electrical network that utilizes communication and information technology to integrate various components in the energy distribution system. IoT technology allows real-time data collection from sensors spread across various points, thus providing accurate information regarding energy consumption, network conditions, and potential disruptions. The research methodology includes designing the IoT system architecture, developing software for data analysis, and testing system performance through simulation and implementation on a limited scale. The data obtained is analyzed using an artificial intelligence (AI)-based predictive algorithm to detect anomalies and provide recommendations for energy distribution management. The results of the study show that the developed system is able to increase energy distribution efficiency by up to 25% and reduce the duration of disruptions by up to 40%. In addition, this system allows for faster and data-based decision making in energy management. In conclusion, the development of an IoT-based smart grid system can be an innovative solution to face the challenges of electricity distribution in the modern era, while supporting the implementation of sustainable energy.